Sensitivity of the acute flaccid paralysis surveillance system for poliovirus in South Africa, 2016‐2019. Issue 10 (October 2021) - Howard, Wayne; Moonsamy, Shelina; Seakamela, Lerato; Jallow, Sabelle; Modiko, Faith; du Plessis, Heleen; Sibiya, Rosina; Kamupira, Mercy; Maseti, Elizabeth; Suchard, Melinda
Abstract : Introduction. : Global poliovirus eradication is a public health emergency of international concern. The acute flaccid paralysis (AFP) surveillance programme in South Africa has been instrumental in eliminating polioviruses and keeping the country poliovirus free. Gap statement. : The sensitivity of surveillance for polioviruses by every African country is of global interest in the effort to ensure global health security from poliovirus re‐emergence. Aim. : To describe the epidemiology of polioviruses from AFP cases and environmental samples in South Africa and to report the performance of the AFP surveillance system for the years 2016‐2019 against targets established by the World Health Organization (WHO). Methods. : Stool specimens from AFP or suspected AFP cases were received and tested as per WHO guidelines. Environmental samples were gathered from sites across the Gauteng province using the grab collection method. Concentration was effected by the two‐phase polyethylene glycol method approved by the WHO. Suspected polioviruses were isolated in RD and/or L20B cell cultures through identification of typical cytopathic effects. The presence of polioviruses was confirmed by intratypic differentiation PCR. All polioviruses were sequenced using the Sanger method, and their VP1 gene analysed for mutations. Results. : Data from 4597 samples (2385 cases) were analysed from the years 2016‐2019. Two cases of immunodeficiency‐associated vaccine‐derived poliovirus (iVDPV) type 3 were detected in 2017 and 2018. A further 24 Sabin type 1 or type 3 polioviruses were detected for the 4 years. The national surveillance programme detected an average of 3.1 cases of AFP/100000 individuals under 15 years old (2.8/100000‐3.5/100000). The stool adequacy of the samples received was 53.0% (47.0‐55.0%), well below the WHO target of 80% adequacy. More than 90% of results were released from the laboratory within the turnaround time (96.6%) and non‐polio enteroviruses were detected in 11.6% of all samples. Environmental surveillance detected non‐polio enterovirus in 87.5% of sewage samples and Sabin polioviruses in 12.5% of samples. Conclusion. : The AFP surveillance programme in South Africa is sensitive to detect polioviruses in South Africa and provided no evidence of wild poliovirus or VDPV circulation in the country.